New principals’ leadership and school culture: A study of three primary schools facing challenging circumstances in Trinidad and Tobago - Lee-Piggott, Rinnelle (My University, 2016)
The literature on new principals tends to focus on the challenges of incumbents. However, there is little detailed evidence of the nature of their attempts at reshaping or enhancing school culture, which may be their greatest single professional challenge. A significant number of primary schools in Trinidad and Tobago are currently headed by new principals and concerns have been publicly raised at the national level about these new principals’ fit to schools. This study was designed to investigate the nature of the interactions between new principals’ leadership and their inherited school cultures in primary schools of different effectiveness states—high, average, and low achievement—which face challenging circumstances. It also investigates the impact of these interactions on school processes, new principals’ emotions and professional development, and student academic outcomes. The study adopts an explanatory, multiple-case study approach, which conceptualizes principal leadership as relational; recognizing that while a new principal may wish to re-culture and restructure a school, the existing school’s culture and the new principal’s own professional judgment may combine to influence his/her ability to do so. The main research method used for engaging with this work was a critical incident technique. Findings reveal the complex nature of the leadership-school culture interplay and the factors that influence: (a) the various manifestations of the leadership-school culture interactions, and, b) the degree of change observed at the schools. Associated implications and areas for future research are also discussed.
Ph.D., University of Nottingham, 2016. ix, 421 p.
Keywords: Beginning principals; Primary school principals; Primary schools; School administration; Organizational culture; Educational leadership; Trinidad and Tobago